تحضير ميكروسفيرات الألجينات الحاوية على الأموكسيسللين بطريقة الاستحلاب/ التهلّم الداخلي - مدني, فاتن; الهوشي, لمى; أحمد, سوسن (Latakia University Journal -Medical Sciences Series, 2019)
يهدف هذا البحث إلى تحضير شكل صيدلاني حديث متناهٍ في الصغر يسمى كريات دقيقة microspheres غير محضّر حتى الآن على مستوى الصناعة الصيدلانية المحلية, باستخدام متماثر ألجينات الصوديوم, ليكون التطبيق الأول لتقانة التمحفظ الدقيق microencapsulation. تمّ اختيار مادة الأموكسيسللين ثلاثي الماءات كنموذج للمادة الدوائية المراد تحضير كريات دقيقة منها, وتمّ تطبيق طريقة التهلّم الداخلي enternal gelation لكبسلة الأموكسيسللين.وبتطبيق هذه الطريقة وتحت شروط معينة تمّ الحصول على كريات دقيقة للأموكسيسللين بشكل كروي وأبعاد وسطية بين 19.06و26.06 ميكرون. ووصلت نسبة الكبسلة حتى61.05%. تمت دراسة تأثيرات متغيرات الصياغة وشروط العمل على أبعاد الكريات الدقيقة وعلى نسبة الكبسلة, إذ ازدادت الأبعاد بزيادة كمية المتماثر المستخدم, ولم تتأثر بتغيير كمية الأموكسيسللين أو العامل المشبك(Ca2+) وتناقصت بزيادة سرعة التحريك. أما نسبة الكبسلة فازدادت بزيادة كمية ألجينات الصوديوم, وزيادة كمية المادة الفعّالة (إلى حدّ معين) وتناقصت بزيادة كمية العامل المشبك (Ca2+) وكذلك بزيادة سرعة التحريك. the aim of this study is to prepare a new and very tiny pharmaceutical dosage form (microsphere) which has not been prepared till now by the local pharmaceutical industry. the microspheres are prepared using sodium alginate, to be the first in microencapsulation technology application. amoxicilline trihydrate was chosen as a model drug for preparing alginate microspheres. the internal gelation method was applied to prepare alginate microspheres containing amoxicilline trihydrate. amoxicilline microspheres with spherical shape and mean diameter ranging between 19 and 26 micron have been obtained, and encapsulation efficiency reached 61.05%. the effect of formulation and operation paramteres on both the size of microspheres and encapsulation efficiency (ee%) has been studied. the mean diameter increased with increasing sodium alginate quantity, and not affected by amoxicilline and crosslinking agent (ca2+) quantities. the size decreased with increasing speed agitation. the encapsulation efficiency increased continuously with sodium alginate quantity, but it increased just to a certain limit with increasing amoxicilline quantity, whereas it decreased with increasing the crosslinking agent (ca2+) quantity and speed agitation.